Ceramic datums and history: Sotho-Tswana pottery in southern Africa - Huffman, Thomas N. (Southern African Humanities, 2020)
The combined use of linguistics, oral traditions and ceramic styles clarifies the complex history of Sotho-Tswana people in southern Africa. The relevant ceramic sequence, known as Moloko, begins in the fourteenth century with the Icon facies in Limpopo, rather than near the confluence of the Marico and Crocodile rivers where traditions place the origins of the Hurutshe cluster. Instead, the Hurutshe cluster, including Kgatla, can be associated with the later Madikwe facies. The ruling line of the Pedi is said to have been Kgatla who left the Rustenburg area in about AD 1650, at about the same time that some Kwena moved to Free State and incorporated Fokeng; in both cases this is before Tswana speakers adopted stonewalling. On the northern plateau, Marateng pottery, the progenitor of the present-day style, is also derived from Madikwe. The pottery of the Hananwa, living around the Blouberg since about the mid-seventeenth century, has a common origin with Marateng, while the pottery of another North Sotho people living near Tzaneen, the Lobedu, does not. In all, seven styles are made by Sotho-Tswana today. These macro styles can be used as datums, along with their antecedents, to investigate political alliances and other forms of interaction. KEY WORDS: Macro styles, Moloko, Sotho-Tswana, southern Africa, traditional pottery.